Differences in the Knowledge and Experience of Physicians and Dentists About Medication-Related Osteonecrosis of the Jaw in Osteoporotic Patients - Masashi Yamori; Mitsumasa Tamura; Masaki Mikami; Toshio Mori; Masaharu Noi; Yoshisato Machida; Shinya Koshinuma; Gaku Yamamoto (Elsevier, 2021)
Aim: Prevention of medication-related osteonecrosis of the jaw (MRONJ) in patients with osteoporosis requires the cooperation of physicians and dentists. We investigated the knowledge, experience, and behaviour related to medical and dental cooperation for MRONJ prevention in patients with osteoporosis between physicians and dentists practising in the Shiga prefecture. Materials and methods: We conducted a cross-sectional study to investigate the cooperation between practising physicians and dentists for preventing osteonecrosis of the jaw (ONJ) in patients with osteoporosis using 2 separate questionnaires from July 28, 2018, to February 3, 2019. Results: Of 461 dentists who were sent the questionnaires at their dental clinics, 307 (67%) responded via fax. Of 846 physicians who were sent the questionnaire at their clinics, 378 (45%) responded via fax. Of these, 268 (32%) were finally analysed because 110 (13%) physicians had never treated patients with osteoporosis; 50% dentists and 24% physicians were familiar with the MRONJ position paper in Japan, and 39% dentists and 9% physicians had encountered MRONJ in their clinical practice. A total of 30% physicians had requested oral health care by a dentist before administering bone-modifying agents (BMA) therapy. The knowledge and experience of MRONJ differed between physicians and dentists. Conclusion: The behaviour of physicians and dentists was insufficient to enable medical and dental cooperation for the prevention of MRONJ in patients with osteoporosis. The lack of cooperation between physicians and dentists during osteoporosis treatment in the Shiga prefecture in Japan is documented in this study.